A study of etiology and role of bacteria in the pigment gall stone diseases at a tertiary care hospital - Desai, Rajendra; Prasad, Earnest Daniel; G., Satyanarayana; V., Lakshmi; Joshi, Nayana (International Surgery Journal, 2018)
Background: Calculus disease of the biliary tract continues to be a significant health problem. Pigment stones are more common in Eastern studies. Predisposing factors such as cirrhosis, ileal resection are commonly seen in the West; while infection as a cause predominates in South East Asia. In this study we prospectively studied Pigment gall stones to examine the causes for and the role of bacteria in pigment Gall stone disease Methods: A hospital based prospective study was carried out from January 1992 to December 1994 at Nizam’s Institute of Medical Sciences, Hyderabad. Institutional Ethics Committee permission was taken. Informed consent was obtained from all selected patients. During the study period a total of 25 consecutive patients with Pigment gall stones were analyzed. Details were recorded in a proforma. Stones were collected from the Gall Bladder with aseptic precautions. Results: Total of 25 patients included, wherein 13 (52%) males and 12 (48%) females. The Median age was 55.5 years and the mean age was 50.2 years. Of 25 patients 11 (44%) had black pigment stones and 14 (56%) had brown stones. 22 (88%) patients presented with biliary colic, and 8 (32%) presented with chronic cholecystitis. At surgery 14 (56%) had a thickened wall suggesting inflammation, 7 (28%) had edema. Bile culture was positive in 11 (44%) patients and stone culture in 5 (20%) patient. Twenty two of 25 patients (88%) had evidence of bacteria on electron microscopy. Conclusions: Whether black stones are associated with higher infection rates or bacteria cause black stones – this question probably would never be answered either on the bench or in the clinicians ward. We, however, can definitely say they are intimately related.